Kontribusi Muhammad Iqbal's Thought Contribution in Islamic Law Renewal - Veranica Safitri (PT FORMOSA CENDEKIA GLOBAL, 2022)
Muhammad Iqbal's thought patterns, especially in the renewal of Islamic law in India, were influenced by the dynamics of European society and their understanding of the Qur'an and al-hadith as sources of ethics that were able to keep up with the times. The ability of the Koran to provide solutions to increasingly broad and complex problems lies in the ability of Muslims to understand especially its legal content. Likewise, the hadith that claim the meaning of character is deep. According to him, changes to the ijtihad mechanism must be carried out, namely the authority of ijtihad which has been with certain people or is individual to collective ijtihad. This view has drawn criticism from both the Muslims themselves and the western orientalist assumptions adopted from the concept of imam in the Catholic religion.